Evaluasi Implementasi Kebijakan Pengelolaan Sampah di Kota Bandung - Muthi Janatun; Ida Rosiana; Riva Kansa Reza; Ivan Darmawan (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
The purpose of this study is to determine and evaluate the evaluation of the Department of Environment and Hygiene (DLHK) on the implementation of the Bandung City waste management policy. The purpose of this type of descriptive research with a qualitative approach is to fully understand the phenomena experienced by the research subject by means of a description in the form of words and language, in a special natural context and by utilizing various scientific methods. The results showed that the waste management policy in Bandung City has been evaluated, but not maximized because there are still problems related to evaluation criteria such as effectiveness, efficiency, adequacy, equity, responsiveness and suitability. Bandung City Regional Regulation Number 9 of 2018 concerning Waste Management, but the Government has not been able to solve the problem because there are still TPS that exceed the capacity so that it disturbs the comfort of the community around the TPS.